Effects of Mouth Breathing on Craniofacial Growth and Oral Health in Children - Dilara Ziylan; Oya Aktören (Çocuk Dergisi)
Mouth breathing in children is a health problem that can cause serious problems in terms of general health, craniofacial development, and oral health. Developmental failures, sleep quality disorders, atypical swallowing, speech disorders, dental caries, gingivitis, adenoid facial shape, and skeletal malocclusions can be seen in mouth breathing children. In these cases, malocclusions such as narrowed maxilla, a deeper palatal vault, posterior cross bite, increased overjet, and anterior open bite can be observed. Early diagnosis of aetiological factors and multidisciplinary treatment approaches are of great importance for children with mouth breathing. This review aimed to emphasize the relationships between mouth breathing and craniofacial/occlusal development and oral health, and to report on the clinical studies and the treatment approaches on this subject.